Pharmacodynamics of Voriconazole against Wild-Type and Azole-Resistant Aspergillus flavus Isolates in a Nonneutropenic Murine Model of Disseminated Aspergillosis - Rudramurthy, Shivaprakash M. (Antimicrob Agents Chemother, 2016)
Invasive aspergillosis (IA) due to Aspergillus flavus is associated with high mortality. Although voriconazole (VRC) is widely recommended as the first-line treatment for IA, emergence of azole resistance in Aspergillus spp. is translating to treatment failure. We evaluated the efficacy of voriconazole in a nonneutropenic murine model of disseminated A. flavus infection using two voriconazole-resistant isolates (one harboring the Y319H substitution in the cyp51C gene) and two wild-type isolates without mutations. All isolates exhibited a dose-response relationship, and voriconazole treatment improved mouse survival in a dose-dependent manner. At 40 mg/kg of body weight, 100% efficacy was observed for 1 susceptible isolate and 1 resistant isolate (with mutation), whereas for another susceptible isolate and resistant isolate (without mutation), survival rates were 81% and 72%, respectively. The Hill equation with a variable slope fitted the relationship between the area under the concentration-time curve (AUC)/MIC ratio and 14-day survival well for each strain. An F test showed the 50% effective doses to be significantly different from each other (P = 0.0023). However, contrary to expectation, there was a significant difference in exposure-response relationships between strains, and it appeared that the susceptible strains required a relatively higher exposure than the resistant ones to result in the same treatment effect, the 50% effective pharmacokinetic/pharmacodynamic (PK/PD) index (EI(50)) required being negatively and log-linearly related to the MIC (P = 0.04). We conclude that the efficacy of voriconazole depended on drug exposure and the voriconazole MIC of the isolates, but lower exposures are required for strains with higher MICs. These findings may have profound significance in clinical practice with respect to dosing and drug choice.